Monitoring Capabilities of the Omron HJ-720ITC Pedometer. Issue 1 (February 2014) - Rider, Brian C.; Bassett, David R.; Thompson, Dixie L.; Steeves, Elizabeth Anderson; Raynor, Hollie
Abstract: Purpose: The purpose of our study was to examine the monitoring capabilities of the Omron HJ-720ITC pedometer and determine the feasibility of using it in physical activity interventions.Methods: Using data from an 8-week lifestyle-intervention study, we tested the capabilities of the pedometer for recording physical activity data. Data from a total of 28 subjects were used in our analysis. The total number of patient steps per day was recorded over the duration of an intervention, as well as "aerobic steps per day" (ie, those taken at a cadence of > 60 steps per minute for ≥ 10 consecutive minutes). Daily wear time was computed in order to ascertain participant compliance in wearing the pedometer. In addition, aerobic steps per minute were computed, providing an assessment of activity intensity during continuous walking bouts.Results: Total steps per day and aerobic steps per day increased from baseline assessment to Week 8. Participants exceeded 100 steps/minute for 89% of their aerobic minutes, suggesting that they were in the moderate-intensity range (3–6 metabolic equivalent tasks) when performing continuous bouts of walking (> 10 minutes).Conclusion: The new pedometer is a reasonably priced, wearable activity monitor that is feasible for use in clinical and research settings.